First occurrence of the invasive alien species Polydora cornuta Bosc, 1802 (Polychaeta: Spionidae) on the coast of Greece (Elefsis Bay; Aegean Sea) - SIMBOURA, N.; SIGALA, K.; VOUTSINAS, E.; KALKAN, E. (Mediterranean Marine Science, 2008)
The present study reports on the occurrence of two specimens of the alien species Polydora cornuta Bosc, 1802, in Elefsis Bay, the Saronikos Gulf (Aegean Sea, eastern Mediterranean). This is the first record of this invasive alien species on the coast of Greece and the second report in the eastern Mediterranean Sea after its first finding in Izmir Bay (on the Turkish Aegean coast). This finding enhances its distributional pattern within the Mediterranean